Ciclesonide exhibits lung-protective effects in neonatal rats exposed to intra-amniotic enterotoxin - Mielgo, Victoria; Gastiasoro, Elena; Catozzi, Chiara; Ricci, Francesca; Gomez-Solaetxe, Miguel A.; Murgia, Xabier; Rey-Santano, Carmen (Frontiers in Pediatrics, 2024)
Introduction Despite the advances in perinatal care, bronchopulmonary dysplasia (BPD) continues to be a highly prevalent chronic lung disease that affects newborns, especially affecting premature newborns. There is no specific cure for BPD, and treatments aimed at reducing the risk of developing BPD focus mainly on lung-protective ventilation strategies, surfactant therapy, and/or corticosteroid administration. Our objective was to evaluate whether systemic postnatal administration of a new glucocorticoid, ciclesonide, can attenuate the alteration of lung structure and pulmonary hypertension in a rat model of chorioamnionitis-induced BPD, with minimal adverse effects on the developing brain. Methods Endotoxin (ETX) or saline was administered to pregnant rats by intra-amniotic (i.a.) injection on day 20 of pregnancy, and pups were delivered by cesarean section on day 22. Ciclesonide (0.5 mg/kg) was administered postnatally for five consecutive days to pups previously exposed to i.a. ETX. On postnatal day 14, we assessed lung function (compliance), lung structure (radial alveolar count, mean linear intercept, pulmonary vessel density), pulmonary hypertension, and brain histology (edema, inflammation, apoptosis, hemorrhage, and infarction). Result On postnatal day 14, the effects of i.a. ETX administration were evident in neonatal rats not receiving treatment; these animals showed impaired lung compliance, disrupted lung structure, and developing pulmonary hypertension compared to those receiving i.a. saline. Postnatal administration of ciclesonide for 5 days was associated with significantly better outcomes in terms of lung compliance, alveolarization, lung vascular growth, and pulmonary hypertension, without affecting the brain histological parameters evaluated. Conclusion Postnatal ciclesonide administration preserved lung function and structure and prevented pulmonary hypertension in a BPD model induced by antenatal i.a. ETX administration, without causing any adverse effects on brain development. These findings suggest that the new glucocorticoid, ciclesonide, may provide a novel strategy for the prevention of BPD; however, more long-term studies are required.